2008
DOI: 10.1007/s10681-008-9654-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci of frost tolerance and physiologically related trait in faba bean (Vicia faba L.)

Abstract: In faba bean, field based winter-hardiness is a complex trait that is significantly correlated to frost tolerance. Frost tolerance could be used to indirectly select for faba bean winter-hardiness. The aim of this study was to identify putative QTL associated with frost tolerance and auxiliary traits and to quantify the efficiency of marker assisted selection. Thus, 101 recombinant inbred lines derived from the cross between two frost tolerant lines were tested for their hardened and unhardened frost tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 38 publications
2
59
2
1
Order By: Relevance
“…Arbaoui and Link (2008) found that fatty acid composition was found to be related to frost tolerance in faba bean. Arbaoui et al (2008b) out lined that five putative quantitative trait loci (QTL) related with fatty acids in faba bean were detected for frost tolerance. Recently Link et al (2010) underlined that three QTLs were identified for frost tolerance (explaining 8.6% of the phenotypic variation).…”
Section: Discussionmentioning
confidence: 99%
“…Arbaoui and Link (2008) found that fatty acid composition was found to be related to frost tolerance in faba bean. Arbaoui et al (2008b) out lined that five putative quantitative trait loci (QTL) related with fatty acids in faba bean were detected for frost tolerance. Recently Link et al (2010) underlined that three QTLs were identified for frost tolerance (explaining 8.6% of the phenotypic variation).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular approaches in faba bean breeding have been mostly limited to biotic stresses and anti-nutritional compounds (reviewed in Torres et al 2010Torres et al , 2012, but amongst abiotic stresses, some progress has also been made in identifying QTLs in frost tolerance (Arbaoui et al 2008). Yield, its components, and flowering time (associated with drought avoidance) were fine mapped in faba bean (CruzIzquierdo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Faba beans shoots were found to contain much more glycinebetaine (125 μ moles per g dry weight) than Phaseolus vulgaris and Pisum sativum shoots where, moreover, trigonelline instead of glycinebetaine was found (Jones and Storey 1981). A number of carbohydrates have also been reported to show a protective impact (Dumont et al 2009), such as raffinose for petunia (Pennycooke et al 2003) and trehalose in Lotus japonicus (López et al 2006;Arbaoui et al 2008b).…”
Section: Resistance To Freezing and Waterloggingmentioning
confidence: 99%